Benefit From Nonsurgical Treatment for Asymptomatic Pancreatolithiasis. Issue 5 (16th May 2022) - Yamamoto, Satoshi; Inui, Kazuo; Katano, Yoshiaki; Miyoshi, Hironao; Kobayashi, Takashi; Tachi, Yoshihiko
Abstract : Objective: Clinical guidelines consider abdominal pain an indication for nonsurgical treatment of pancreatolithiasis. We examined benefit from nonsurgically treating asymptomatic pancreatolithiasis. Methods: We retrospectively reviewed 165 patients with pancreatolithiasis who underwent nonsurgical treatment between 1992 and 2020. Symptoms were absent in 41, while 124 had abdominal pain. In the asymptomatic group, the median follow-up duration was 8 months (range, 0–166 months), and the median age was 61 years (range, 32–80 years). In patients with pain, the median follow-up duration was 43 months (range, 0–293 months), while the median age was 57 years (range, 22–80 years). The male:female ratio was 3.6:1 for asymptomatic patients and 5.9:1 for those with pain. We compared treatment outcome, stone recurrence rate, and changes in pancreatic exocrine function (bentiromide- p -aminobenzoic acid test results) between groups. Results: Nonsurgical treatment for patients with asymptomatic pancreatolithiasis had a 63% stone clearance rate, lower than 84% for symptomatic pancreatolithiasis but comparable to outcomes at other institutions. Pancreatic exocrine function values during the year after treatment were mean, 52% (standard deviation, 16%) in the asymptomatic group, similar to mean, 57% (standard deviation, 17%) in the symptomatic group. Conclusions: Nonsurgical treatment in asymptomatic pancreatolithiasis may preserve pancreatic exocrine function as well as in symptomatic pancreatolithiasis.